The Influence of Financial Literacy and Digital Financial Competency on Advanced consumption of Student Behavior: The Mediating Role of Self-Control in Wuhan University of Technology in China - Houbianbian; Fridayana Yudiaatmaja; Putu Indah Rahmawati (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The rapid expansion of the digital economy and fintech infrastructure has fundamentally restructured the consumption patterns of university students, leading to a rise in credit-enabled advanced consumption. This research aims to investigate the determinants of advanced consumption behavior by integrating cognitive financial assets and psychological self-regulation mechanisms. Specifically, the study examines the influence of financial literacy and digital financial competency on advanced consumption, with self-control serving as a potential mediating variable. A quantitative research design was employed, utilizing Structural Equation Modeling (SEM) to analyze data collected from university students. The empirical results demonstrate that both financial literacy and digital financial competency exert a significant negative influence on advanced consumption behavior. Notably, digital financial competency emerged as a more potent predictor, suggesting that in a platform-mediated economy, the ability to navigate digital choice architecture is a critical deterrent to excessive spending. Furthermore, the analysis reveals that self- control significantly mediates the relationship between these financial capabilities and consumption outcomes. Approximately 39% of the impact of financial knowledge on reducing debt-funded consumption is transmitted through the strengthening of internal regulatory mechanisms.These findings underscore the necessity of a holistic approach to financial education. Beyond traditional numeracy, academic and policy interventions should prioritize critical digital literacy and the development of psychological resilience. Strengthening the "cognitive shield" of digital competency and the "behavioral filter" of self-control is essential to safeguard students from the systemic risks of a frictionless credit environment and to ensure long-term financial well-being in the digital era.